2018
DOI: 10.1002/ccr3.1701
|View full text |Cite
|
Sign up to set email alerts
|

Atrial fibrillation, an epiphenomenon of acute Stanford type‐A aortic dissection with suspected intimo‐intimal intussusception

Abstract: Key Clinical MessageSupraventricular arrhythmias can sometimes be “only” epiphenomena appearing during acute hypoxia, pneumonia, pulmonary embolism, and thrombosis. Indeed, atrial fibrillation is not rare in acute aortic dissection as it is estimated in about one half of patients and may be secondary to a perfusion deficit of the sinoatrial node artery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 10 publications
(13 reference statements)
0
3
0
Order By: Relevance
“…AD, which might involve coronary injury, pericardial involvement, and other direct cardiac effects, could increase the risk of AF . However, there is no argument made in support of an association between AD and subsequent AF although several molecular mechanisms involving the atrial remodeling and weakness of the aortic walls might be possible explanations .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…AD, which might involve coronary injury, pericardial involvement, and other direct cardiac effects, could increase the risk of AF . However, there is no argument made in support of an association between AD and subsequent AF although several molecular mechanisms involving the atrial remodeling and weakness of the aortic walls might be possible explanations .…”
Section: Discussionmentioning
confidence: 99%
“…Aortic dissection (AD) is a life threating disease once left undiagnosed or untreated . The phenomenon of AD presenting with atrial fibrillation (AF) has indeed been discussed previously; in case of subclinical AD, AF may occur and be a sign of alert. For clinicians who care for patients with AF, it is well known that stroke, heart failure, and death are common AF complications .…”
Section: Introductionmentioning
confidence: 99%
“…After the first modern literature report in 1962, 7 there were approximately 61 aortic intimal intussusception (AII) studies reported until now, and most of them were case reports. Among them, 55 (90%) involved the natural progression of type A aortic dissection, 817 and only 1 reported the complication during transcatheter aortic valve replacement. 18 For TBAD, AII was also demonstrated in natural progression, blunt trauma, and iatrogenic cases from angiography catheter injury.…”
Section: Discussionmentioning
confidence: 99%